Reactive Coatings in Glass Capillaries: Preparation of Temperature‐ and Light‐Responsive Surfaces and Accurate Determination of Wettability Switching. Issue 1 (2nd December 2015) - Wagner, Natalie; Kessler, Daniel; Theato, Patrick
Abstract : The inner walls of thin glass capillaries are coated with a reactive precursor coating that can be converted into different temperature‐ and light‐responsive coatings. The switching range of wettability can be determined by measuring the meniscus height of water inside these capillaries at different temperatures and upon UV‐light irradiation. In comparison with the sessile drop measurement, very accurate equilibrium contact angles are obtained by this method. Abstract : In the present paper, the synthesis and characterization of new thermo‐ and light‐responsive copolymers are described that are derived from alkylamines and their switchable wettability behavior as surface coatings. The switching range of the wettability can be determined by measuring the meniscus height of water inside capillaries at different temperatures and upon UV‐light irradiation.